1971
DOI: 10.5636/jgg.23.169
|View full text |Cite
|
Sign up to set email alerts
|

The O1 Component of the Geomagnetic Lunar Daily Variation

Abstract: Geomagnetic data from twelve stations have been analyzed for O1 lunar tidal variations by the Chapman-Miller method. Well-determined geomagnetic O1 tides were found in the vertical component at several stations. In most cases little or no solar modulation of the fundamental frequency of the O1 (Z) tide was detected, thus making an ionospheric source for the O1(Z) tide unlikely. The most probable cause of the O1(Z) variation is electric currents induced in the oceans by O1 tidal currents. No definite conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…As discussed below, lunar variations in the neutral atmosphere can lead to changes in ionospheric parameters such as electron density and electric and magnetic fields. The most important lunar variation occurs at the lunar semidiurnal ( M 2 ) period of 12.42 hr, although some brief mention has been made in the literature of the quasi‐diurnal lunar component (O 1 , period = 25.82 hr) on the basis of ionospheric and geomagnetic observations (Chapman, ; Fejer & Tracy, ; Jones & Jones, ; Pedatella & Forbes, ; Tarpley, ; Winch, ). The diurnal lunar tide is introduced by the inclination of the Moon's orbit with respect to Earth's equatorial plane.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed below, lunar variations in the neutral atmosphere can lead to changes in ionospheric parameters such as electron density and electric and magnetic fields. The most important lunar variation occurs at the lunar semidiurnal ( M 2 ) period of 12.42 hr, although some brief mention has been made in the literature of the quasi‐diurnal lunar component (O 1 , period = 25.82 hr) on the basis of ionospheric and geomagnetic observations (Chapman, ; Fejer & Tracy, ; Jones & Jones, ; Pedatella & Forbes, ; Tarpley, ; Winch, ). The diurnal lunar tide is introduced by the inclination of the Moon's orbit with respect to Earth's equatorial plane.…”
Section: Introductionmentioning
confidence: 99%
“…Pedatella and Forbes [] observed the diurnal lunar tide as well; however, there are few studies about this oscillation in the ionosphere and the mechanism of generation is poorly understood. For instance, Tarpley [] pointed out the ocean tide as a likely source for the diurnal lunar tide in the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The results of WINCH (1970WINCH ( , 1971, TARPLEY (1971), RAO and SASTRI (1974) and SASTRI et al (1975) have indicated that O1 tide is able to produce detectable variations in the geomagnetic field. The time dependence of L(O1), which is determined by the product of the terms representing lunar diurnal atmospheric tidal movement and the time variation of electrical conductivity of the ionosphere, restricted to the first two harmonics, is given by: 3 L(O1)-csin(nt-2-h+2) vn ( 1) where c,, is the amplitude of the nth harmonic, t is mean solar time increasing *Forms part of the author's Ph .…”
Section: Introductionmentioning
confidence: 92%
“…It is likely that each such transient variation might contribute to the numerical estimate of the other. In fact, the results of WINCH (1970) andTARPLEY (1971) indicated the presence of such contamination. WINCH (1970) suggested that appropriate adjustments made for the effect of L(O1), may substantially reduce the seasonal variation of L(M2) and may, thus, offer an explanation for the unduly large seasonal variation observed in global L(M2).…”
Section: Introductionmentioning
confidence: 93%